2015
DOI: 10.1053/j.ajkd.2015.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Failure and ESRD in the Atherosclerosis Risk in Communities (ARIC) Study: Comparing Ascertainment of Treated and Untreated Kidney Failure in a Cohort Study

Abstract: Background Linkage to the US Renal Data System (USRDS) registry is commonly used to identify end-stage renal disease (ESRD) cases, or kidney failure treated with dialysis or transplantation, but it underestimates the total burden of kidney failure. This study validates a kidney failure definition that includes both kidney failure treated and not treated by dialysis or transplantation. It compares kidney failure risk factors and outcomes using this broader definition to USRDS-identified ESRD risk factors and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 27 publications
0
48
0
Order By: Relevance
“…Use of hospitalization data has been shown to be a valid method for defining ESRD and is more representative of the overall burden of kidney disease by incorporating treated and untreated kidney disease including deaths due to kidney disease. 40,41 We previously reported that, compared to medical record review, our composite definition including ICD-9/10 codes for hospitalizations has a sensitivity of 88% and specificity of 97%. 41 Assessment of free and bioavailable 25(OH)D was based on calculations rather than direct measurement.…”
Section: Discussionmentioning
confidence: 98%
“…Use of hospitalization data has been shown to be a valid method for defining ESRD and is more representative of the overall burden of kidney disease by incorporating treated and untreated kidney disease including deaths due to kidney disease. 40,41 We previously reported that, compared to medical record review, our composite definition including ICD-9/10 codes for hospitalizations has a sensitivity of 88% and specificity of 97%. 41 Assessment of free and bioavailable 25(OH)D was based on calculations rather than direct measurement.…”
Section: Discussionmentioning
confidence: 98%
“…Direct comparison estimates across studies is hampered by differences in study design, data coverage, methodology and reporting. For example, probability samples, such as NHANES or ARIC, require participants to volunteer, inevitably excluding sicker individuals [30]. On the other hand, healthcare utilization cohorts, such as this one, may overestimate CKD estimates since non-users of the health system are excluded.…”
Section: Discussionmentioning
confidence: 99%
“…29 eGFR was calculated using these values and the Chronic Kidney Disease Epidemiology Collaboration equation. 33 Cases of ESRD were determined through linkage to the US Renal Data System registry 34 ; eGFR at the time of ESRD onset was imputed as 15 ml/min per 1.73 m 2 . In sensitivity analysis, we also included eGFR abstracted from intervening cardiovascular hospitalizations.…”
Section: Outcome Assessmentmentioning
confidence: 99%